OPHTHALMOSAURUS MONOCHARACTUS APPLEBY (REPTILIA, ICHTHYOPTERYGIA), EN LAS CALIZAS LITOGRAFICAS TITONIANAS DEL AREA LOSCATUTOS, NEUQUÉN, ARGENTINA (Ameghiniana, 2013)
A juvenil of Ophthalmosaurus monocharactus Appleby is described. It was found in tithonian lithographic shales from Los Catutos area, Departament of Zapala, Neuquén Province, Argentina. This new record, in the South American Oriental Pacific, enlarges geographic and temporal range of this species, frequently recorded in the Oxford Clay of England. Likewise, Ancanamunia mendozana (Rusconi) is considered Ophthalmosaurus sp.